THE ESSENCE AND CURRENT SIGNIFICANCE OF THE ORGANIZATION OF MANAGEMENT ACCOUNTING IN BUSINESS ENTITIES (Academicia Globe: Inderscience Research, 2026)
This article discusses the organization of management accounting in business entities, its application in accounting and significance. The author also developed recommendations for improving management accounting.